#TITLE_ALTERNATIVE# - PRABU HARYASUKMA (NIM: 12214079), KRESNA
An evaluation of CO2-EOR equation of U.S. Department of Energy (DOE) is presented in this study. A guideline parameter for U.S. DOE equation from the previous study that was based on literature and expert technical judgement was used to calculate CO2 flooding performance in Field B, South Sumatera. The calculation result was compared with simulation result that uses actual field data from Field B to validate the accuracy of the equation. CO2 flooding was performed in three prospective blocks of Field B (block B1, B2, and B4) that were selected based on oil saturation distribution. Before CO2 flooding was performed, the reservoir has been waterflooded to meet the requirement of U.S. DOE equation. Reservoir simulation was conducted using a compositional commercial simulator. The result of the simulation was used as the benchmark for evaluation. The difference between calculation result and simulation result was observed. A new parameter that was based on simulation result was also constructed to provide a better approximation with a lower difference. The new parameter was then categorized based on oil saturation to be used as the improved guideline parameter for U.S DOE equation. This study concluded that oil recovery difference resulted from calculation using U.S. DOE equation with guideline parameter yields differences from simulation result of 25457 STB for block B1, 57006 STB for block B2, and 51252 STB for block B4, and recovery factor differences from simulation result of 5% for block B1 and B2 and 4% for block B4. The result was already good enough due to its low difference, means that the U.S. DOE equation with guideline parameter is quite reliable to use. The difference occurred due to mismatching assumption used in the guideline parameter determination. The calculation with new parameter yields a better result with lower difference. The new parameter was then categorized into moderate oil saturation and low oil saturation and used as the improved guideline parameter. The novelty of U.S. DOE equation is that it provides an easier means of obtaining the same result from simulation using the more efficient method. The improved guideline parameter for U.S. DOE equation provided in this study can be used to give a better approximation in obtaining oil recovery from other areas in the Field B.